Persepsi Pegawai Terhadap Gaya Kepemimpinan Atasan di Dinas Pendidikan Kota Padang Panjang - Yenti , Guspera (Jurnal Ilmu Hukum, Humaniora dan Politik, 2022)
Abstract: The research background shows that the phenomenon of leadership is not yet optimal in the application of good leadership styles to employees in the office. This research is intended to obtain information about employee perceptions of the leadership style of the Padang Panjang City Education Office in improving the implementation of employee duties in a task-oriented leadership style and subordinate-oriented leadership style. The population is the Padang Panjang City Education Office employees, totaling 74 people. The total sample of 44 people was taken using the Proportional Stratified Random Sampling technique. The data collection tool in this study was a questionnaire, a Likert Scale model that had been tested for validity and reliability; with valid and reliable results. Data analysis techniques use the average formula. The results of the research on employee perceptions of the implementation of the leadership style of the Padang Panjang City Education Office are in the pretty good category with an overall average score of 64.61%. Abstrak: Latar belakang penelitian yang menunjukkan fenomena kepemimpinan belum optimalnya penerapan gaya kepemimpinan yang baik pada pegawai di kantor. Penelitian ini dimaksudkan untuk memperoleh informasi tentang persepsi pegawai terhadap gaya kepemimpinan Dinas Pendidikan Kota Padang Panjang dalam meningkatkan pelaksanaan tugas pegawai pada gaya kepemimpinan berorientasi tugas dan gaya kepemimpinan berorientasi bawahan. Populasinya adalah pegawai Dinas Pendidikan Kota Padang Panjang yang berjumlah 74 orang. Jumlah sampel sebanyak 44 orang yang diambil dengan menggunakan teknik Proportional Stratified Random Sampling. Alat pengumpulan data dalam penelitian ini adalah kuesioner, model Skala Likert yang telah diuji validitas dan reliabilitasnya; dengan hasil yang valid dan terpercaya. Teknik analisis data menggunakan rumus rata-rata. Hasil penelitian persepsi pegawai terhadap penerapan gaya kepemimpinan Dinas Pendidikan Kota Padang Panjang dalam kategori cukup baik dengan nilai rata-rata keseluruhan sebesar 64,61%.